Management of locally advanced or metastatic combined hepatocellular cholangiocarcinoma - Zhao, Jemmy; Stephan-Falkenau, Susann; Schuler, Markus; Arndt, Börge (Cancers, 2023)
Combined hepatocellular cholangiocarcinoma (cHCC-CC) is a rare primary liver malignancy that comprises features of hepatocellular carcinoma (HCC) and cholangiocarcinoma (CC). Due to the rarity of this tumor, the treatment of choice has not yet been defined. For resectable disease, liver resection is the mainstay treatment. However, most patients relapse or display advanced disease and were not surgical candidates. Although the majority of patients are either primarily or secondarily treated in palliative intent, no guideline recommendations or prospective trial reports exist to allow reliable evaluation of debated treatment options. We review different locoregional or medical treatment options for advanced combined hepatocellular cholangiocarcinoma (cHCC-CC) in the neoadjuvant, adjuvant, or palliative setting and discuss the possibility of predictive biomarker-guided therapeutic options.